(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Gun Culture indicates that there is normalization of gun in society, but unaware of the consequences it holds for every one. It refers to exploitation of firearms due to easy availability and supply of illegal weapons from overseas at very low cost. Different states like UP, Bihar, Punjab, J&K and Rajasthan had witnessed operation of unlicensed weapons. Due to gun in many states India faces a serious issue. There are very strict laws for firearms in India, there are many loopholes from where criminals and normal citizens acquire guns. There are so many reasons from portraying themselves as pow erful person or to threatening someone or to protecting and even killing someone. Few surveys shows that the numbers of licensed firearms are very low as compared to unlicensed firearms. So many sever measures taken by government and police to bring an end to the gun culture, but corruption and politics have given hope to the culprits. Thus, this mixed article tries to bring out this situation, reasons and solutions for the prevailing evil form of gun culture in India with a case report. In our case there was multiple open firing done with country made firearm at Jam-Packed place over a pity argument between two local bhai/goons leading to death of one amongst them. After conducting a detailed postmor tem examination at our esteemed institute, it took a whole new different path in which Two Entry wounds & single Exit wound is found with no evidence of any bullets, pellets or any other projectile object inside any body cavity. Internal ricochet phenomenon was observed